Great women of India. - Madhavananda,Swami.,Ed.; Majumdar,Ramesh Chandra.,Ed. (Mayavati, Almora, Himalayas : Advaita Ashrama, 1953)
On the ideals of Indian womanhood.
"The holy Mother birth centenary memorial."
Keywords: Women. -- India